Structural similarity between bovine conglutinin and bovine lung surfactant protein D and demonstration of liver as a site of synthesis of conglutinin. - Lim, B L (1993)
Conglutinin is a Ca(2+)-dependent, carbohydrate-binding, serum protein which contains an N-terminal collagen-like region and a C-terminal, C-type lectin domain. To date, conglutinin, which appears to play an important role in defence mechanisms, has been fully described, by protein sequence analysis, only in the bovine system. To allow comparison of lung surfactant protein D (SP-D) with conglutinin, within one species, a full-length cDNA clone for SP-D has been isolated from a bovine lung library. The derived amino acid sequence for bovine SP-D shows a higher (78%) level of identity to the sequence of conglutinin than to the sequence of human or rat SP-D (67 and 65% respectively). However, SP-D and conglutinin are known to have different carbohydrate-binding specificities, therefore some of the 16 residues conserved in the C-type lectin domains of all three species of SP-D, but which are not conserved in conglutinin, appear likely to be involved in determination of specificity. The use of a polymerase chain reaction (PCR)-derived DNA probe for bovine SP-D in Northern blotting studies yielded a signal from bovine liver mRNA as well as the expected signal from bovine lung mRNA. Since SP-D appears to be a lung-specific protein, it seems probable that the liver is the primary site of synthesis of conglutinin.